The impact of social media information exposure on appearance anxiety in young acne patients: a moderated chain mediation model - Zhang, Zhijian; Zhou, Min (Frontiers in Psychology, 2024)
The boom of social media has provided a wider space for ordinary people to display themselves, but visual presentation has also intensified the focus on appearance, which in turn triggers anxiety about appearance. The study aims to investigate the impact of social media information exposure on appearance anxiety in young acne patients and the pathways and mechanisms that cause this effect. A moderated chain mediation model was constructed, and a questionnaire was used to collect information on social media information exposure, internalization of beauty ideals, fear of negative evaluation, self-esteem, and appearance anxiety in young acne patients (N=382), and the relationships between the variables were explored through regression analysis. The results show that there was a significant path of effect (t>2.5, P<0.05) between social media information exposure, internalization of beauty ideals, fear of negative evaluation, and appearance anxiety. Self-esteem significantly moderated the relationship between social media information exposure and internalization of beauty ideals (t<-2, P<0.05). In conclusion, in young acne patients, internalization of beauty ideals and fear of negative evaluation chain mediated the association between social media information exposure and appearance anxiety, and young acne patients' internalization of beauty ideals was inversely correlated with their level of self-esteem.